Improvement of the Technologi Packaging for the Transportation of Mangosteen - Niluh Yulianti; Sutrisno .; Emmy Darmawati (Jurnal Keteknikan Pertanian, 2010)
AbstractThe research aimed to design a package made of corrugated board for mangosteen packaging; test the compression strength of the packaging; analyze the effect of packaging capacity and fruit packing pattern in the container on some quality parameters after transport, and analyze the economy of the packaging used.The research was conducted in three stages, namely: the measurement of physical and mechanical properties of fruit (Stage I); the packaging design i.e. determining the packaging dimension (Stage II); and packaging design testing (Stage III). Compression and vibration testing were conducted. For the vibration testing, transport simulations were conducted using the vibration simulator of 3.50 Hz and amplitude of 4.61 cm for 3 hours. The packaging was designed with a capacity of 8 kg and 15 kg using two packing pattern, namely the fcc and Jumble. Based on the physical and mechanical properties, optimal packing pattern of 8 kg container was 8, 4, and 4 pieces of fruit for the long x, y, and z direction, respectively, with the density of 62%. Therefore, gave packaging dimension of 39.4 x 21 x 21 cm. For the 15 kg container, the optimal packing pattern was 8, 6 and 5 pieces of fruit for the x, y, and z direction, respectively, with the packing density of 65.6%. Thus, gave dimension of 39.4 x 30 x 25 cm. Based on overall test results, it can be stated that the design packaging capacity of 8 kg with dimension of 39.4 cm x 21 cm x 21 cm and the fcc packing pattern gave the optimal setting for mangosteen transportation.Keywords: packaging design, fcc, jumble, transportation, mangosteenDiterima: 18 September 2009; Disetujui: 25 Februari 2010